2014
DOI: 10.1088/0067-0049/215/1/14
|View full text |Cite
|
Sign up to set email alerts
|

THE WISE BLAZAR-LIKE RADIO-LOUD SOURCES: AN ALL-SKY CATALOG OF CANDIDATE γ-RAY BLAZARS

Abstract: We present a catalog of radio-loud candidate γ-ray emitting blazars with WISE mid-infrared colors similar to the colors of confirmed γ-ray blazars. The catalog is assembled from WISE sources detected in all four WISE filters, with colors compatible with the three-dimensional locus of the WISE γ-ray emitting blazars, and which can be spatially cross-matched with radio sources from either one of the three radio surveys: NVSS, FIRST and/or SUMSS. Our initial WISE selection uses a slightly modified version of prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 45 publications
6
81
0
1
Order By: Relevance
“…The separation between the mid-IR colors of the Fermi blazars and that of other sources randomly chosen appears evident. The presence of BZBs in the region of the "WISE Gamma-ray Strip" occupied by the BZQs is only limited to a handful of sources (see e.g., D 'Abrusco et al 2013;D'Abrusco et al 2014, for more details). The dashed polygon marks the region used to select potential RWBLs.…”
Section: Bzbs Wds and Welqs At Mid-ir Wavelengthsmentioning
confidence: 99%
“…The separation between the mid-IR colors of the Fermi blazars and that of other sources randomly chosen appears evident. The presence of BZBs in the region of the "WISE Gamma-ray Strip" occupied by the BZQs is only limited to a handful of sources (see e.g., D 'Abrusco et al 2013;D'Abrusco et al 2014, for more details). The dashed polygon marks the region used to select potential RWBLs.…”
Section: Bzbs Wds and Welqs At Mid-ir Wavelengthsmentioning
confidence: 99%
“…A compact radio core is detected. This radio galaxy has been previously classified as a possible BL Lac object (D'Abrusco et al 2014).…”
Section: Notes On Candidate Hymorsmentioning
confidence: 99%
“…Several sources were already reported as blazar candidates in WIBRaLS (D'Abrusco et al 2014, marked as WBR in the following Table 2) or as QSO by Brescia et al (2015, B15 in Table 2), or their flat radio spectrum was confirmed by low frequency data Massaro et al (2014, M14 in Table 2); one is in the 1WHSP sample (1WH in Table 2), but not reported in Paper II because the cluster has 5 photons, lower than the minimum number considered in that paper. Only for one source we found a possible correspondence with a high energy source reported in the 3EG catalogue (Hartman et al 1999), but up to now undetected in the Fermi sky.…”
Section: Mstmentioning
confidence: 99%